Identification of criteria and indicators for hazardous trees in Recreation Forest of Selangor, Malaysia. - Yaman, Amat Ramsa; Ariffin, Noor Syakila; Mohd, Abdullah; Yip, Hin Wai; Maruthaveeran, Sreetheran (Faculty of Forestry, Universiti Putra Malaysia, 2008)
Recreation forest is a popular setting for outdoor recreation in Selangor, Malaysia. In the recreation forest, hazardous trees in this setting can be associated with risks in which the manager of the forest needs to give serious attention. A study was conducted to identify the criteria and indicators in evaluating hazardous trees in these forests. Delphi technique was used to gather a consensus on the characteristics related to criteria and indicators of hazardous trees. This technique allows the respondents some flexibility while selecting appropriate criteria and indicators involving three rounds of interviews with respondents. The respondents are staff of the State Forestry Department of Selangor who are experts in recreational forest landscape. The final outcome of the Delphi process was the identification of 17 criteria and 51 indicators in evaluating trees in recreational forest. From the findings of this study, the State Forestry Department of Selangor can use the identified criteria and indicators as guidelines in their hazardous tree management. This would help managers in making correct decision on hazardous tree problems and increase public awareness on the existence of those trees in their surroundings.